Bolivia : 2018 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
After years of impressive growth and poverty reduction, Bolivia is facing a more challenging period. Accommodative fiscal and monetary policies combined with lower gas and minerals prices have contributed to continued large twin deficits, foreign reserve losses, and a sharp increase in public debt. External competitiveness has been negatively affected by the appreciating US dollar, high wage growth, and domestic policies that have hindered private sector investment. A definitive change in the policy stance is warranted to restore external balance, minimize a further buildup in vulnerabilities, and promote broad based growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet